Health Spending and Political Influence. Issue 2 (March 2015) - Leider, Jonathon P.; Tung, Greg; Castrucci, Brian; Sprague, James B.
<x xml:space="preserve">Abstract</x> Earmarks, otherwise known as Congressionally directed spending requests, are a historically significant means of political influence over budgets. In this brief, we report on the results of a longitudinal study of federal earmarks affecting health care facilities and public health. We analyzed 10 years of earmark for health care facilities and examined the correlates of being in the top 50% of earmark recipients for each year. Having representatives or senators serving on the respective Appropriations committees were shown to have increased odds of being a top earmark recipient, as was being in jurisdictions with greater poverty. However, health-related measures of need were not significantly associated with being a top earmark recipient.